2016
DOI: 10.3390/ijerph13121250
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Pedestrian Head Injuries—Collision Parameter Relationships through a Combination of Retrospective Analysis and Finite Element Method

Abstract: There are a very limited number of reports concerning the relationship between pedestrian head injuries and collision parameters through a combination of statistical analysis methods and finite element method (FEM). This study aims to explore the characteristics of pedestrian head injuries in car–pedestrian collisions at different parameters by using the two means above. A retrospective analysis of pedestrian head injuries was performed based on detailed investigation data of 61 car–pedestrian collision cases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Studies have pointed out that vehicle collision velocity has the most significant effect on pedestrian head injuries, especially under a back impact [10, 11]. Congruent with these studies, we observed that head injuries tended to be more prevalent in with-traffic crashes where pedestrians were struck from behind, particularly in rural settings where collision velocities tended to be higher.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Studies have pointed out that vehicle collision velocity has the most significant effect on pedestrian head injuries, especially under a back impact [10, 11]. Congruent with these studies, we observed that head injuries tended to be more prevalent in with-traffic crashes where pedestrians were struck from behind, particularly in rural settings where collision velocities tended to be higher.…”
Section: Discussionsupporting
confidence: 69%
“…Such a beneficial effect of walking against traffic is attributable to the visual information it provides regarding vehicles in the lane closest to pedestrians. Han et al [10] and Liu et al [11] have reported that pedestrians who were struck from behind were more likely to sustain head injuries, which are normally devastating or fatal.…”
Section: Introductionmentioning
confidence: 99%
“…Head or neck injuries had higher mortality than injuries to extremities or pelvic girdles. High mortality from head injuries was reported in previous studies, such as in Kenya, Laos, Vietnam, Libya, and China [6,19,21,26,46]. This might be due to most drivers and passengers not wearing helmets, despite their use being required by law.…”
Section: Discussionmentioning
confidence: 87%
“…However, the impactor lacks a sensor that can observe the instantaneous speed and acceleration at the impact location. These sensors are more direct indexes to describe the degree of injury in an animal (Liu et al, 2016; Wu et al, 2016) than the impact pressure, and we will add the sensor in future experiments.…”
Section: Discussionmentioning
confidence: 99%